Isa-isa lang! - Santiago, Pablo
The billiard ball is round... like the life of Carding (Fernando Poe, Jr.) who revolves around the billiard table earn a living and survive together with his small family. Being a real master of the said game, he has been used by rich gamblers to enjoy their vices and laid down their big bets. The ball rolls and so is his life when he was falsely accused of playing the game backward. His return was a treat as he tried to use his palm as the billiard table and his enemies, the balls.